2004
DOI: 10.1080/01612840490486818
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping Among Cardiovascular Nurses: A Survey in Brazil

Abstract: Cardiovascular nurses are frequently involved in critical patient care, providing support to patients and their families. The goals of this study were to survey a representative sample of cardiovascular nurses, describe ways of coping, and identify sources of stress in the hospital setting. A descriptive and correlational survey design was used. A self-completed questionnaire was distributed to 76 nurses from a cardiovascular hospital in São Paulo City, Brazil. The measures were the Nursing Stress Evaluation Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
2
22
0
3
Order By: Relevance
“…4,5 Other studies in Brazil have found informal social support to be negatively correlated with domestic violence 6 and positively related to coping with job stress. 7 Likewise, satisfaction with family relations has been associated with older women's quality of life. 8 Because supportive relationships and reciprocal obligations are socially constructed and culturally defined, 9 it is possible that roles and values of kinship relations vary by social class.…”
mentioning
confidence: 99%
“…4,5 Other studies in Brazil have found informal social support to be negatively correlated with domestic violence 6 and positively related to coping with job stress. 7 Likewise, satisfaction with family relations has been associated with older women's quality of life. 8 Because supportive relationships and reciprocal obligations are socially constructed and culturally defined, 9 it is possible that roles and values of kinship relations vary by social class.…”
mentioning
confidence: 99%
“…En el ámbito asistencial, existe consenso entre los especialistas en clasificar las fuentes de estrés en dos grandes grupos: organizacionales y extraorganizacionales. Entre los principales estresores organizacionales se destacan la sobrecarga (Zacché Avellar, Iglesias, & Fernández Valverde, 2007); los conflictos y la falta de apoyo de superiores y colegas (Salmond & Ropis, 2005); la falta de recursos, tanto humanos como materiales (Grunfeld et al, 2005); la presión del tiempo (Ferraz Bianchi, 2004) y los bajos salarios, que generan una elevada percepción de inequidad (Montanholi, Tavares, & Oliveira, 2006).…”
Section: Estrés Laboral Asistencialunclassified
“…Entre las debilidades hay que remarcar la composición de la muestra en estudio, ya que por haber estado integrada por disponibilidad impediría la generalización de los resultados a toda la población de profesionales de la salud argentinos. No obstante y, en sintonía con lo puntualizado por un gran número de investigadores en el área (Ferraz Bianchi, 2004;Salmond & Ropis, 2005;Skytt, Ljunggren & Carlsson, 2007), como en la composición de la muestra se incluyeron representantes de las más diversas instituciones asistenciales del medio, los resultados obtenidos podrían considerarse un fiel reflejo de la situación asistencial local. Otra limitación del estudio podría estar referida al carácter auto descriptivo de la mayoría de los instrumentos empleados para la recolección de los datos.…”
Section: Fortalezas Limitaciones Y Sugerencias Para Futuros Estudiosunclassified
“…The nursing professional experiences stressors within his daily activity. The situation of dealing with the extreme states of life and death can be represented as a stressor by the nurse, an event that can be interpreted as a challenge (a positive event in his work) in the interactionist model's primary appraisal, or as a threat (a negative event in his performance); in both conditions, however, the event is deemed as stressing and thus demands stress physiological and behavioral reflections (4)(5)(6) .…”
Section: Conceptual Basismentioning
confidence: 99%